2022
DOI: 10.46610/rrddd.2022.v04i01.001
|View full text |Cite
|
Sign up to set email alerts
|

Botanical, Ethnopharmacological, Phytochemical & Pharmacological Standards of Plant Ichnocarpus frutescens

Abstract: The plant Ichnocarpus frutescens belongs to family Apocynaceae, commonly known as ‘Black creeper’ (In Odia: Syamolota; Hindi: Kali-dudhi, Krishna sariva; Sanskrit: Syamalata, Sariva). It is native to India, China, Java, Ceylon, Southeast Asia, and northern Australia. It is a large, evergreen, woody climbing plant. In India, tribes used this plant as a substitute of Indian Sersaparilla (Hemidesmus indicus). Phytochemical investigation indicates that plant belong to various category viz. phytosterol, triterpenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Due to their low reduced glutathione (GSH) content and high iron concentration, which impairs their ability to scavenge oxygen radicals, OLGs are particularly susceptible to oxidative stress [91] . Additionally, it has been shown that membranes rich in cholesterol, such as those present in OLGs and myelin, are more vulnerable to damage by Aβ 42 oligomers [92] . Aβ 42 oligomers engage a number of membrane receptors on neurons and astrocytes, including the p75 neurotrophin receptor (p75NTR), frizzled receptor, insulin receptor, NMDA glutamate receptor, and 7 nicotinic ach receptor, according to earlier studies on the pharmacology of Aβ receptors (a7n).…”
Section: Comparison Of Neuropathologic Criteria For the Diagnosis Of ...mentioning
confidence: 99%
“…Due to their low reduced glutathione (GSH) content and high iron concentration, which impairs their ability to scavenge oxygen radicals, OLGs are particularly susceptible to oxidative stress [91] . Additionally, it has been shown that membranes rich in cholesterol, such as those present in OLGs and myelin, are more vulnerable to damage by Aβ 42 oligomers [92] . Aβ 42 oligomers engage a number of membrane receptors on neurons and astrocytes, including the p75 neurotrophin receptor (p75NTR), frizzled receptor, insulin receptor, NMDA glutamate receptor, and 7 nicotinic ach receptor, according to earlier studies on the pharmacology of Aβ receptors (a7n).…”
Section: Comparison Of Neuropathologic Criteria For the Diagnosis Of ...mentioning
confidence: 99%
“…Compared to the single herb, the polyherbal formulation has better and extended therapeutic potential. Ichnocarpus frutescens, Ficus dalhousie, Crateva magna, Alpinia galangal, and Swertia chiraita are well-known plants available throughout India and they are commonly used for the treatment of various diseases including diabetes mellitus (F.P. et al, 2022;Faheem I P et al, 2021;FP et al, 2018).…”
Section: Introductionmentioning
confidence: 99%